2021
DOI: 10.1080/13574809.2021.1968295
|View full text |Cite
|
Sign up to set email alerts
|

Using suitability analysis, informed by Co-Design, to assess contextually appropriate urban growth models in Gulu, Uganda

Abstract: Uganda has one of Africa's fastest urban growth rates, compounding urban challenges, including urban sprawl, the proliferation of informal settlements, decrepit housing, and the privatization of urban development without providing public open space and transport connectivity. In response, this paper tests generic models of urbanization that could be applied in Uganda. This evaluation is conducted through a suitability analysis, informed through Co-Design activities, of the city of Gulu in Northern Uganda. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…This growth appears to mount enormous pressure on both localand urban authorities to provide essential services as well as spur the muchneeded development objectives of the urbanizing population. A few of the challenges identified include unsustainable water supply, sanitation and hygiene (Bishoge, 2021), urban liveability and prosperity (Nastar, Isoke, Kulabako, & Silvestri, 2019), urban slump, the explosion of slums, dilapidated housing, and the denationalization of urban growth lacking public greeneries and transport plans (Bolleter et al, 2022), non-communicable diseases (Mackay, 2022), and water pollution (Okurut, Kulabako, Chenoweth, & Charles, 2015), to mention just a few. Even though the country's level of urban sprawl is moderately low, with just 18% of its populace living in cities and towns, it is one of the most rapidly urbanizing countries in Africa.…”
Section: The Context Of Cdfs In Ugandamentioning
confidence: 99%
“…This growth appears to mount enormous pressure on both localand urban authorities to provide essential services as well as spur the muchneeded development objectives of the urbanizing population. A few of the challenges identified include unsustainable water supply, sanitation and hygiene (Bishoge, 2021), urban liveability and prosperity (Nastar, Isoke, Kulabako, & Silvestri, 2019), urban slump, the explosion of slums, dilapidated housing, and the denationalization of urban growth lacking public greeneries and transport plans (Bolleter et al, 2022), non-communicable diseases (Mackay, 2022), and water pollution (Okurut, Kulabako, Chenoweth, & Charles, 2015), to mention just a few. Even though the country's level of urban sprawl is moderately low, with just 18% of its populace living in cities and towns, it is one of the most rapidly urbanizing countries in Africa.…”
Section: The Context Of Cdfs In Ugandamentioning
confidence: 99%
“…Other models require more complex datasets such as demographics, demand, transportation zones, centers of attractions, and more. More comprehensive studies can be found in the field of connectivity of the public transport network, where the social needs of people, the difference in the accessibility of public transport depending on the territory, can be taken into account (Currie, 2010;Bolleter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%